2016
DOI: 10.1007/s10529-016-2162-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechano-growth factor E peptide promotes healing of rat injured tendon

Abstract: MGF-C25E plays an important role in promoting healing of injured rat tendon and could be used as a potential therapeutic factor for tendon repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…MGF injection was reported as a reliable therapeutic method in an in vivo study, where Deng et al injected 28.5-and 57-μg/kg body weight MGF into the bone deflection area of rabbits to promote osteogenesis and demonstrated that high-dose MGF treatment is more effective in bone repair than low-dose treatment. Zhang et al injected MGF into the ankle joints of rats for tendon repair and reported that 1-μg/ml-MGF treatment had a superior result (Zhang, Luo, Chen, et al, 2016;Zhang, Luo, Kuang, Ju, & Song, 2016). In the present study, three different MGF treatment doses (0.1-10 μg/ml) were used for OA cartilage repair.…”
Section: Discussionmentioning
confidence: 73%
“…MGF injection was reported as a reliable therapeutic method in an in vivo study, where Deng et al injected 28.5-and 57-μg/kg body weight MGF into the bone deflection area of rabbits to promote osteogenesis and demonstrated that high-dose MGF treatment is more effective in bone repair than low-dose treatment. Zhang et al injected MGF into the ankle joints of rats for tendon repair and reported that 1-μg/ml-MGF treatment had a superior result (Zhang, Luo, Chen, et al, 2016;Zhang, Luo, Kuang, Ju, & Song, 2016). In the present study, three different MGF treatment doses (0.1-10 μg/ml) were used for OA cartilage repair.…”
Section: Discussionmentioning
confidence: 73%
“…Healing/migratory percentages were estimated compared to t0 of the respective cell type using the formula: 100-(area in t16 or t30 or t48 / area in t0) ×100. Respective p-values were generated comparing the differences in healing in the same time points (16,30…”
Section: Cell Cultures Treatments and Stable Transfectionsmentioning
confidence: 99%
“…MGF is a growth factor that was first identified in mechanically stimulated skeletal muscle 10,11 . Subsequently, MGF was found in many other tissues, such as ischemic tissue of brain, 12 stromal cells of the eutopic endometrium, 13 malignancies, 14 osteoblasts, 15 growth plate chondrocytes 16 et al Studies have confirmed that MGF is involved in the repair and regeneration process of muscles, 17 bones, 18 nerves, 19 tendons, 20 cartilage, 16 and many other tissues and organs under biomechanical environments after damage. It even showed outstanding performance in enhancing skeletal muscle movement 21 .…”
Section: Introductionmentioning
confidence: 99%